Cassava molecular genetics and genomics for enhanced resistance to diseases and pests - Ntui, V.O.; Tripathi, J.; Kariuki, S.M.; Tripathi, L. (Wiley, 2024)
Cassava (Manihot esculenta) is one of the most important sources of dietary calories in the tropics, playing a central role in food and economic security for smallholder farmers. Cassava production is highly constrained by several pests and diseases, mostly cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). These diseases cause significant yield losses, affecting food security and the livelihoods of smallholder farmers. Developing resistant varieties is a good way of increasing cassava productivity. Although some levels of resistance have been developed for some of these diseases, there is observed breakdown in resistance for some diseases, such as CMD. A frequent re-evaluation of existing disease resistance traits is required to make sure they are still able to withstand the pressure associated with pest and pathogen evolution. Modern breeding approaches such as genomic-assisted selection in addition to biotechnology techniques like classical genetic engineering or genome editing can accelerate the development of pest- and disease-resistant cassava varieties. This article summarizes current developments and discusses the potential of using molecular genetics and genomics to produce cassava varieties resistant to diseases and pests.